Protective effects and potential mechanisms of fermented egg-milk peptides on the damaged intestinal barrier - Lyu, Siwen; Yang, Qi; Duan, Xuehui; Liu, Xuanting; Du, Zhiyang; Shang, Xiaomin; Xu, Menglei; Liu, Jingbo; Pan, Fengguang; Zhang, Ting (Frontiers in Nutrition, 2022)
Introduction Fermented egg-milk peptides (FEMPs) could enhance the colon-intestinal barrier and upgrade the expression of zonula occludens-1 and mucin 2. Besides, the underlying biological mechanism and the targets FEMPs could regulate were analyzed in our study. Methods Herein, the immunofluorescence technique and western blot were utilized to evaluate the repair of the intestinal barrier. Network pharmacology analysis and bioinformatics methods were performed to investigate the targets and pathways affected by FEMPs. Results and discussion Animal experiments showed that FEMPs could restore intestinal damage and enhance the expression of two key proteins. The pharmacological results revealed that FEMPs could regulate targets related to kinase activity, such as AKT, CASP, RAF, and GSK. The above targets could interact with each other. GO analysis indicated that the targets regulated by FEMPs could participate in the kinase activity of the metabolic process. KEGG enrichment revealed that the core targets were enriched in pathways related to cell apoptosis and other important procedures. Molecular docking demonstrated that FEMPs could bind to the key target AKT via hydrogen bond interactions. Our study combined the experiment in vivo with the method in silico and investigated the interaction between peptides and targets in a pattern of multi-targets and multi-pathways, which offered a new perspective on the functional validation and potential application of bioactive peptides.